Optimizing surgical precision: a comparative study of three-port vs. four-port robotic-assisted lobectomy for NSCLC - Fangfang Yang; Lei Chen; Hui Wang; Qianyun Wang; Chen Yang (Journal of Cardiothoracic Surgery)
Abstract Background In recent years, robot-assisted thoracoscopic surgery has seen major advances. The feasibility and safety of this new surgical procedure have been widely recognized. However, only a few studies have investigated the short-term postoperative outcomes of lobectomy in early-stage non-small cell lung cancer (NSCLC) patients using different numbers of ports in Da Vinci robot-assisted surgery. This study aimed to evaluate the clinical value of robot-assisted lobectomy by comparing the perioperative data of NSCLC patients who underwent three-port and four-port surgical methods. Methods The data of 121 consecutive patients who were admitted to our hospital for NSCLC and underwent Da Vinci robot-assisted thoracic surgery (RATS) for radical resection from January 2020 to October 2021 were retrospectively collected and analyzed. The cases that did not meet the inclusion criteria were removed, and the patients were divided into the three-port group (76 cases) and the four-port group (45 cases). The general clinical data, perioperative data, and postoperative pain were individually compared to determine the different clinical effectiveness of the two approaches. Results All 121 patients in the 2 groups successfully underwent lobectomy and systemic lymph node dissection. No significant difference in age, sex, tumor location, tumor size, history of chronic disease, pathological type, pathological tumor-node-metastasis (pTNM) staging, postoperative complications, and number or stations of total lymph nodes dissected was observed between the two groups (P > 0.05). The operation time [(117.32 ± 36.55) min vs. (136.83 ± 40.63) min], the console time [(90 ± 19.35) min vs. (103 ± 15.65) min], the intraoperative blood loss [(94.34 ± 32.16) mL vs. (102.73 ± 33.67) mL], the chest tube drainage time [(2.43 ± 0.65) d vs. (2.79 ± 1.42) d], and the postoperative hospitalization time [(4.55 ± 1.43) d vs. (5.14 ± 1.66) d] were lower in the three-port group compared to the four-port group but showed no statistically significant difference (P > 0.05). However, the three-port group demonstrated significantly superior visual analogue scale pain scores compared to the four-port group at 24, 48, and 72 h postoperatively (all p < 0.001). Conclusions Compared to four-port RATS, the three-port robotic-assisted lobectomy is safe, practicable and effective. Operative incision optimization leads to less postoperative pain and appears to be more acceptable for patients with NSCLC.